Noncanonical regulation of phosphatidylserine metabolism by a Sec14-like protein and a lipid kinase - Wang, Yaxi; Yuan, Peihua; Grabon, Aby; Tripathi, Ashutosh; Lee, Dongju; Rodriguez, Martin; Lönnfors, Max; Eisenberg-Bord, Michal; Wang, Zehua; Man Lam, Sin; Schuldiner, Maya; Bankaitis, Vytas A. (The Journal of cell biology, 2020)
The yeast phosphatidylserine (PtdSer) decarboxylase Psd2 is proposed to engage in a membrane contact site (MCS) for PtdSer decarboxylation to phosphatidylethanolamine (PtdEtn). This proposed MCS harbors Psd2, the Sec14-like phosphatidylinositol transfer protein (PITP) Sfh4, the Stt4 phosphatidylinositol (PtdIns) 4-OH kinase, the Scs2 tether, and an uncharacterized protein. We report that, of these components, only Sfh4 and Stt4 regulate Psd2 activity in vivo. They do so via distinct mechanisms. Sfh4 operates via a mechanism for which its PtdIns-transfer activity is dispensable but requires an Sfh4-Psd2 physical interaction. The other requires Stt4-mediated production of PtdIns-4-phosphate (PtdIns4P), where Stt4 (along with the Sac1 PtdIns4P phosphatase and endoplasmic reticulum–plasma membrane tethers) indirectly modulate Psd2 activity via a PtdIns4P homeostatic mechanism that influences PtdSer accessibility to Psd2. These results identify an example in which the biological function of a Sec14-like PITP is cleanly uncoupled from its canonical in vitro PtdIns-transfer activity and challenge popular functional assumptions regarding lipid-transfer protein involvements in MCS function.